TOTAL COST OF HOSPITALIZATION OF PATIENTS UNDERGOING ELECTIVE LAPAROSCOPIC CHOLECYSTECTOMY RELATED TO NUTRITIONAL STATUS - MENEZES,Francisco Julimar Correia de (2016)
ABSTRACT Background: In the Western world, the population developed an overweight profile. The morbidly obese generate higher cost to the health system. However, there is a gap in this approach with regard to individuals above the eutrofic pattern, who are not considered as morbidly obese. Aim: To correlate nutritional status according to BMI with the costs of laparoscopic cholecystectomy in a public hospital. Method: Data were collected from medical records about: nutritional risk assessment, nutricional state and hospital cost in patients undergoing elective laparoscopic cholecystectomy. Results: Were enrolled 814 procedures. Average age was 39.15 (±12.16) years; 47 subjects (78.3%) were women. The cost was on average R$ 6,167.32 (±1830.85) to 4.06 (±2.76) days of hospitalization; 41 (68.4%) presented some degree of overweight; mean BMI was 28.07 (±5.41) kg/m²; six (10%) individuals presented nutritional risk ≥3. There was a weak correlation (r=0.2) and not significant (p <0.08) between the cost of hospitalization of the sample and length of stay; however, in individuals with normal BMI, the correlation was strong (r=0,57) and significant (p<0.01). Conclusion: Overweight showed no correlation between cost and length of stay. However, overweight individuals had higher cost of hospitalization than those who had no complications, but with no correlation with nutritional status. Compared to those with normal BMI, there was a strong and statistically significant correlation with the cost of hospital stay, stressing that there is normal distribution involving adequate nutritional status and success of the surgical procedure with the consequent impact on the cost of hospitalization.